2010
DOI: 10.1002/etc.352
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of petroleum hydrocarbon distillates to soil organisms

Abstract: Canadian standards for petroleum hydrocarbons in soil are based on four distillate ranges (F1, C6-C10; F2, >C10-C16; F3, >C16-C34; and F4, >C34). Concerns have arisen that the ecological soil contact standards for F3 may be overly conservative. Oil distillates were prepared and characterized, and the toxicity of F3 and two subfractions, F3a (>C16-C23) and F3b (>C23-C34), to earthworms (Eisenia andrei), springtails (Orthonychiurus folsomi), and northern wheatgrass (Elymus lanceolatus), as well as the toxicity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 19 publications
5
55
0
2
Order By: Relevance
“…Plant toxicity varied with species and endpoint; however, C. canadensis and P. tremuloides were generally more sensitive to the hydrocarbon-impacted soils, all plants considered. However, consistent with other studies [36,37], greater sensitivity was demonstrated by soil invertebrate sublethal endpoints, relative to plant endpoints. Even though test durations were extended for the boreal species to accommodate for their growth rate, differences in toxicity because of test duration was likely not a major contributing factor, because in some cases test endpoints for the boreal plants (e.g., P. banksiana 35-d test) were less sensitive than the standard test species.…”
Section: Discussionsupporting
confidence: 91%
“…Plant toxicity varied with species and endpoint; however, C. canadensis and P. tremuloides were generally more sensitive to the hydrocarbon-impacted soils, all plants considered. However, consistent with other studies [36,37], greater sensitivity was demonstrated by soil invertebrate sublethal endpoints, relative to plant endpoints. Even though test durations were extended for the boreal species to accommodate for their growth rate, differences in toxicity because of test duration was likely not a major contributing factor, because in some cases test endpoints for the boreal plants (e.g., P. banksiana 35-d test) were less sensitive than the standard test species.…”
Section: Discussionsupporting
confidence: 91%
“…Overall the least sensitive endpoint was germination, and the most sensitive endpoint was root growth, but this varied between root and shoot growth depending on the species and the soil type tested (Figure 2, Table 5). Other studies have also shown that germination success is a less sensitive endpoint than root and shoot growth, resulting in an underestimation of the toxicity of fuel-contaminated soils [36,40]. Interestingly for D. chapmanii and E. pendunculare, the order of sensitivity of endpoints was conserved between soil types, but this order differed between soil types for L. crinita and C. muscoides (Table 4).…”
Section: Discussionmentioning
confidence: 92%
“…During hydrocarbon exposures, acute toxicity is likely caused by lighter, more volatile hydrocarbons with a lower equivalent carbon number; heavy fractions with a high equivalent carbon number are more likely to cause chronic toxic effects [34][35][36][37]. Toxicity of petroleum hydrocarbons is strongly correlated with hydrocarbon fractions that have lower boiling points and octanol-water coefficients [log(K ow )], especially those within the nC10-nC19 range [12,[37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Saturated and unsaturated structures composed of hydrogen and carbon make up the largest fraction of organic compounds derived from fossil sources, including crude oil, its derivatives and distillates as well tar oils originating from coal gasification. These are often referred to as petroleum hydrocarbons (Cermak, 2010), also encompassing mono-and polycyclic aromatic structures of environmental and toxicological concern (Loibner et al, 2004).…”
Section: Environmental Pollution With Petroleum Hydrocarbonsmentioning
confidence: 99%